Programmable a-InGaZnO gate array with laser-induced forward transfer. (18th March 2021) - Jo, Youngmin; Kwon, Jimin; van der Steen, Jan-Laurens; Kronemeijer, Auke Jisk; Jung, Sungjune
Abstract: Here, we present a pseudo-CMOS NOR gate array based on dual-gate amorphous indium-gallium-zinc oxide thin-film transistors (TFTs) on plastic. We fabricated a 14 × 12 array of NOR gates which was programmed using laser-induced forward transfer printing technology to realize a negative-edge-triggered D flip-flop. Two drive transistors in a conventional NOR gate configuration were replaced by a single independently gate-controlled dual-gate transistor, which enabled us to design and fabricate a gate array with much reduced number of transistors and interconnects. We anticipate that programmable gate arrays based on dual-gate oxide TFTs can be a new route to design and fabrication of digital circuitry that will be essential for emerging applications Internet-of-Things and wearable electronics.